2006
DOI: 10.1177/0363546506286786
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral Contact Mechanics after Serial Medial Meniscectomies in the Human Cadaveric Knee

Abstract: Because the degree of meniscectomy leading to clinically significant outcomes is unknown, a prudent strategy is to preserve the greatest amount of meniscus possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
351
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(386 citation statements)
references
References 54 publications
20
351
2
1
Order By: Relevance
“…1, right). Pilot work that involved testing and retesting of an intact knee indicated that the osteotomy led to a change in peak contact pressure of approximately 5%; this observation is similar to that reported by Lee et al 28 and by Martens et al 40 , who found that such an osteotomy had little effect on measured joint contact pressure.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…1, right). Pilot work that involved testing and retesting of an intact knee indicated that the osteotomy led to a change in peak contact pressure of approximately 5%; this observation is similar to that reported by Lee et al 28 and by Martens et al 40 , who found that such an osteotomy had little effect on measured joint contact pressure.…”
Section: Methodssupporting
confidence: 83%
“…The model used for this study was based on technology developed to evaluate the wear performance of total knee replacements-i.e., the Stanmore KC Knee Joint Simulator 36 . Unlike static or quasi-static models that provide data at discrete points in the gait cycle, the simulator allows knees to be dynamically and continuously loaded under conditions that simulate gait 28,31,34,48 . It is a force-controlled apparatus than can be programmed to simultaneously and dynamically control the axial force, anterior force, posterior force, and rotational moment (internal/external torque) as a function of the applied flexion/extension angle profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meniscus is vital to normal function and longevity of the knee, as meniscal loss causes increased contact pressures and articular cartilage degeneration [3][4][5][6][7][8] . Meniscal repair techniques have evolved substantially in the last few decades, with open techniques replaced by arthroscopic techniques.…”
mentioning
confidence: 99%
“…The number of meniscectomies for the treatment of meniscal tears has risen dramatically in the last decades, especially with the advancement of arthroscopy. However, the management of meniscal ruptures is currently changing with the better understanding of meniscal function and better knowledge on the short-to-mid-term consequences of meniscectomy on the articular cartilage: osteoarthritis [3][4][5]. As a consequence, nowadays most orthopaedic surgeons try to preserve as much meniscal tissue as possible or make an attempt for meniscal repair [6].…”
Section: Introductionmentioning
confidence: 99%